Automated complex for investigation the properties of dusty plasma in external magnetic field - Masheyeva, R.U.; Dzhumagulova, K.N.; Shalenov, E.O. (Recent Contributions to Physics, 2019)
This chapter discusses the developed automated complex of computer programs for the investigation and simulation of the physical properties of magnetized dusty plasma. Computer simulation of the system was carried out on the basis of molecular dynamics, taking into account the influence of an external uniform magnetic field. The particles of the system interact with the potential of Yukawa. The complex was developed in the Borland Delphi7 object-oriented programming environment, using additional components. The complex consists of several subprograms with the help of which one can investigate the dynamic and structural properties of dusty plasma in an external magnetic field. The complex provides the transfer of information between the user-person and the software and hardware components of the computer system, makes communication with the computer as simple and natural as possible. The interface is as close as possible to the user, and the user can fully control the course of the program. In order to bring the interface as close as possible to the user, familiar terminology, customization of the user's reality, user-friendly interface and interface transparency were used. During calculations using an automated complex, you can change the system parameters, draw a graph of the results obtained, stop and exit the program. On the basis of this complex, the author's certificate “Magnetized Dusty Plasma” was obtained.